Membangun Iman Kristen di Kalangan Suku Dayak Kanayatn Melalui Pendekatan Kontekstual Upacara Adat Kamang Tariu - Nianda Nianda; Theodorus Theodorus; Giri Krispambudi; Yuliawati S. (Makarios: Jurnal Teologi Kontekstual, 2022)
In general, the customs, traditions and culture of each ethnic group differ depending on the geographical location and the way of life of each. Almost all customs and cultural traditions of each ethnic group become a benchmark for ethics, morals and habits that occur and are always positive according to their ethnicity, although there are some other cultural views that consider it not necessarily positive. For the Dayak Kanayatn tribe, traditions, customs and culture are the most important things in managing daily life. Dayak Kanayatn is very thick with tradition and culture. One of the most feared Dayak traditions is the "baparang or bakayo (cut the enemy head)" tradition, because it is related to supernatural powers. The tradition of “baparang or bakayo (cut the enemy head)” for the Dayak Kanayatn tribe cannot be separated from “Kamang Tariu Traditional Ceremony”. It is said that the story of “Kamang Tariu” can give supernatural powers to Dayak people who are going to “baparang or bakayo (cut the enemy head)”, so that they are immune to machetes, fire, rifles and others. In order for this paper to be accurate, the author discusses it using a descriptive method sourced from the existing literature and also from the results of interviews related to the discussion of this article. Then it will look for correlations from a biblical point of view, with contextual approach using the “Kamang Tariu Tradisional Ceremony”, so that the expected results can contribute to building Christian faith among the Kanayatn Dayak tribe.